Otevrené pleurální okénko v lécbĕ pokrocilého empyému hrudníku: zkusenosti s lécbou dvaceti rizikových pacientů - Jedlicka, V; Vlcek, P; Veverková, L; Dolezel, J; Pestál, A; Veselý, M; Zák, J; Capov, I (Rozhledy v chirurgii, 2009)
UNLABELLED: The aim of the retrospective clinical study was the analysis of the 20 high-risk patients operated in our department within years 2000-2008 by the modified Eloesser procedure for the serious thoracic empyema. MATERIAL AND METHODS: We have analyzed the data of the 17 men and 3 women. The most important objectives were the cause of the disease, type of procedure, perioperative mortality, length of stay and subsequent procedures. The underlying disease was the malignant intrathoracic disease in 40%, diabetes mellitus was found in 25%. The cause of empyema was pleuropneumonia in 45%, postresectional empyema occurred in 35%. RESULTS: There were two perioperative deaths (10%), remaining patients were all dismissed in a stabilized condition the 22nd postoperative day at average. Six subsequent reconstructive procedures were performed. There was no early death for the postpneumonectomy empyema. CONCLUSION: In case of the serious pleural empyema in a high-risk patient is the modified Eloesser procedure safe and life saving surgical operation. The timing of the procedure and correct indication for surgery are essential.
Keywords: senioři; senioři nad 80 let; Thoracic Surgical Procedures; hrudní chirurgické výkony; Middle Aged; mužské pohlaví; Pleura; Adult; Aged, 80 and over; pleura; ženské pohlaví; Humans; lidé středního věku; empyém pleurální; dospělí; Thoracostomy; Female; torakostomie; Aged; Empyema, Pleural; lidé; Male